2021
DOI: 10.21203/rs.3.rs-155656/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Genetic Variants of Oxidative Stress Responsive Kinase 1 (OXSR1) with Asthma Exacerbations in Non-Smoking Asthmatics

Abstract: Background: Asthma exacerbation threatens patient's life. Several genetic studies have been conducted to determine the risk factors for asthma exacerbation, but this information is still lacking. We aimed to determine whether genetic variants of Oxidative Stress Responsive Kinase 1(OXSR1), a gene with functions of salt transport, immune response, and oxidative stress, are associated with exacerbation of asthma.Methods: Clinical data were obtained from 1,454 asthmatics and single nucleotide polymorphisms (SNPs)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Two recent studies of Korean subjects with asthma revealed genetic associations for AEs in NLRP4 and OXSR1 that differed by smoking status [51,62]. NLRP4 is a regulator of the inflammasome acting as an inhibitor of type I interferon signalling, tumor necrosis factor (TNF)-α and IL-1β-mediated NF-κB activation [69].…”
Section: Candidate-gene Association Studies Most Candidate-gene Assoc...mentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies of Korean subjects with asthma revealed genetic associations for AEs in NLRP4 and OXSR1 that differed by smoking status [51,62]. NLRP4 is a regulator of the inflammasome acting as an inhibitor of type I interferon signalling, tumor necrosis factor (TNF)-α and IL-1β-mediated NF-κB activation [69].…”
Section: Candidate-gene Association Studies Most Candidate-gene Assoc...mentioning
confidence: 99%
“…NLRP4 is a regulator of the inflammasome acting as an inhibitor of type I interferon signalling, tumor necrosis factor (TNF)-α and IL-1β-mediated NF-κB activation [69]. Conversely, OXSR1 encodes an oxidative stress responsive kinase that participates in ion transport and cell volume homeostasis [62]. In fact, OXSR1 expression was increased by smoke exposure and glucocorticoid treatment in various airway cell types [62].…”
Section: Candidate-gene Association Studies Most Candidate-gene Assoc...mentioning
confidence: 99%
See 1 more Smart Citation